Chemical constituents of the bark of Gallesia gorazema - Barbosa, Luiz CLaudio Almeida; Demuner, Antônio Jacinto; Teixeira, Robson; Madruga, M. S. (Fitoterapia, 1999)
Chemical composition analysis of the essential oil from the bark of Gallesia gorazema was carried out by GC/MS. This analysis led to the identification of six non-sulfurated and 19 sulfurated compounds.
Keywords: Gallesia gorazema; Essential oil; Polysulfides